2021
DOI: 10.3389/frobt.2021.669972
|View full text |Cite
|
Sign up to set email alerts
|

A Long-Term Engagement with a Social Robot for Autism Therapy

Abstract: Social robots are increasingly being used as a mediator between a therapist and a child in autism therapy studies. In this context, most behavioural interventions are typically short-term in nature. This paper describes a long-term study that was conducted with 11 children diagnosed with either Autism Spectrum Disorder (ASD) or ASD in co-occurrence with Attention Deficit Hyperactivity Disorder (ADHD). It uses a quantitative analysis based on behavioural measures, including engagement, valence, and eye gaze dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 41 publications
0
44
0
Order By: Relevance
“…For the experimental articles, we classified the type of robot used in the experiment into five categories: human-like, animal-like, toy-like, machine-like, and wearable robots; From our review, we found that the majority of the articles (ten articles) used a human-like robot in their studies [ 2 , 6 , 9 , 10 , 14 , 18 , 19 , 21 , 24 , 37 ], seven articles used an animal-like robot [ 27 , 28 , 29 , 31 , 32 , 33 , 36 ], five articles used a toy-like robot [ 17 , 20 , 22 , 23 , 30 ], two articles used a machine-like robot [ 25 , 35 ], and only one article used a wearable robot [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the experimental articles, we classified the type of robot used in the experiment into five categories: human-like, animal-like, toy-like, machine-like, and wearable robots; From our review, we found that the majority of the articles (ten articles) used a human-like robot in their studies [ 2 , 6 , 9 , 10 , 14 , 18 , 19 , 21 , 24 , 37 ], seven articles used an animal-like robot [ 27 , 28 , 29 , 31 , 32 , 33 , 36 ], five articles used a toy-like robot [ 17 , 20 , 22 , 23 , 30 ], two articles used a machine-like robot [ 25 , 35 ], and only one article used a wearable robot [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…We found that 40% of the articles (ten articles) used human-like robots. Nao, a well-known (in the market) human-like robot, was used in 32% of the studies (eight articles) [ 2 , 9 , 10 , 14 , 18 , 19 , 24 , 37 ]. Another human-like robot named Kasper was used in two studies [ 6 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were predominantly based on the Applied Behavior Analysis (ABA) principles and targeted socio-emotional behaviors. To this end, we implemented 26 activities in two local languages (Kazakh and Russian) and categorized them into six groups ("Songs", "Dances", "Emotions", "Social Acts", "Imitations", "Storytelling" and "Touch Me" (see Telisheva et al, 2019;Rakhymbayeva et al, 2021). Descriptions of each group are provided in Table 3.…”
Section: Activitiesmentioning
confidence: 99%
“…Long-term engagement: Although cross-sectional studies are commonplace due to different technological and methodological constraints, it is feasible to commit to long-term goals and test the efficacy of NAO and its capabilities. The user studies in robotassisted educational and therapeutic settings need convincing evidence of the robot's long-term efficacy, especially those working with underserved populations (Rakhymbayeva et al, 2021).…”
Section: Future Research With Naomentioning
confidence: 99%